1993
DOI: 10.1523/jneurosci.13-08-03266.1993
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular analysis of relations between the slow (< 1 Hz) neocortical oscillation and other sleep rhythms of the electroencephalogram

Abstract: The newly described slow cortical rhythm (approximately 0.3 Hz), whose depolarizing-hyperpolarizing components are analyzed in the preceding article, is now investigated from the standpoint of its relations with delta (1-4 Hz) and spindle (7-14 Hz) rhythmicity. Regular-spiking and intrinsically bursting cortical neurons were mostly recorded from association suprasylvian areas 5 and 7; fewer neurons were also recorded from pericruciate motor and posterolateral visual areas. Although most cells were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
651
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 823 publications
(698 citation statements)
references
References 49 publications
44
651
1
2
Order By: Relevance
“…2). A broad local peak in the power spectra indicated oscillatory activity associated with the slow oscillation (1 Hz) 34,37 and delta oscillation (1.5-4 Hz), which predominate under anaesthesia and natural sleep and can be observed in states of quiet wakefulness 27,33,34 . As in our DC-EEG and LFP recordings of spontaneous activity, we observe the presence of substantial power in the infraslow frequency (o0.1 Hz) range indicating a significant presence of infraslow spontaneous activity in our cortical VSD signals ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). A broad local peak in the power spectra indicated oscillatory activity associated with the slow oscillation (1 Hz) 34,37 and delta oscillation (1.5-4 Hz), which predominate under anaesthesia and natural sleep and can be observed in states of quiet wakefulness 27,33,34 . As in our DC-EEG and LFP recordings of spontaneous activity, we observe the presence of substantial power in the infraslow frequency (o0.1 Hz) range indicating a significant presence of infraslow spontaneous activity in our cortical VSD signals ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering work by Steriade and colleagues has shown that identified neurons in a number of different cortical areas fluctuate between depolarized (UP) and hyperpolarized (DOWN) states[29,30,31]. The UP state is characterized by barrages of synaptic activity, a plateau depolarization, and action potential firing, while the DOWN state is characterized by cell hyperpolarization and silence[30] (Fig.…”
Section: Neuronal Substrates Of Slow Oscillationsmentioning
confidence: 99%
“…Interestingly, although the isolated cortical slices and cortical slabs can generate slow oscillations independently of the thalamus[30,47,50,51], there has been no formal quantitative analysis of the characteristics of cortical slow oscillations in the absence of the thalamus[52]. A recently proposed view of the slow oscillation suggests that this rhythm is generated by a synaptic-based cortical oscillator and two intrinsic thalamic oscillators: thalamocortical neurons and neurons of the TRN[52].…”
Section: Neuronal Substrates Of Slow Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is further doubt that the effect can be a result of a high susceptibility of subcortical structures such as the thalamus since sleep spindles can be generated in the cortex alone [Steriade et al, 1993]. Their 87% duty cycle versus the usual GSM digital phone cycle of 12.5% may be a factor.…”
Section: Electroencephalography and Evoked Responsesmentioning
confidence: 99%